Psychopaths and blame : the argument from content - Levy, N (Routledge, 2014)
The recent debate over the moral responsibility of psychopaths has centered on whether, or in what sense, they understand moral requirements. In this paper, I argue that even if they do understand what morality requires, the content of their actions is not of the right kind to justify full-blown blame. I advance two independent justifications of this claim. First, I argue that if the psychopath comes to know what morality requires via a route that does not involve a proper appreciation of what it means to cause another harm or distress, the content of violations of rules against harm will be of a lower grade than the content of similar actions by normal individuals. Second, I argue that in order to intend a harm to a person—that is, to intend the distinctive kind of harm that can only befall a person—it is necessary to understand what personhood is and what makes it valuable. The psychopath's deficits with regard to mental time travel ensure that s/he cannot intend this kind of harm.